„Zamknij drzwi”, czyli wykorzystanie przestrzeni filmowej do uobecnienia sacrum na przykładzie filmu Sieranevada Cristi Puiu - Przybylski, Krystian (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2020)
The article analyzes how the main representative of the Romanian New Wave – Cristi Puiu – uses the visual space of an apartment for staging and presenting the visible and hidden spheres of reality. His film Sieranevada, focusing on a family meeting on the occasion of religious ceremonies commemorating recently deceased senior family member, shows the possibilities of using the language of realism to appeal to the spirituality present in everyday life and to unveil Transcendence.